2020
DOI: 10.1016/j.cortex.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

How to do things with (thousands of) words: Computational approaches to discourse analysis in Alzheimer's disease

Abstract: Natural Language Processing (NLP) is an ever-growing field of computational science that aims to model natural human language. Combined with advances in machine learning, which learns patterns in data, it offers practical capabilities including automated language analysis. These approaches have garnered interest from clinical researchers seeking to understand the breakdown of language due to pathological changes in the brain, offering fast, replicable and objective methods. The study of Alzheimer's disease (AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 102 publications
1
52
0
Order By: Relevance
“…However, there have been efforts in the past few years to simplify the procedure and to develop standardized measures for discourse analysis (Dalton et al 2019 ). Additionally, recent advances in computational linguistics are promising, with major components of the analyses being automatized, making the process less time consuming and less error-prone (Aluisio et al 2016 ; Clarke et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been efforts in the past few years to simplify the procedure and to develop standardized measures for discourse analysis (Dalton et al 2019 ). Additionally, recent advances in computational linguistics are promising, with major components of the analyses being automatized, making the process less time consuming and less error-prone (Aluisio et al 2016 ; Clarke et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, speech and handwriting data can be acquired at low cost and without any distress to the patient. Speech has proven to be a suitable modality for diagnosing Alzheimer's disease [65,66] and Parkinson's disease Countless convolutional neural network architectures can be used, but they often share similar common concepts as convolutional, pooling, and dense layers. ResNet50 [60], EfficientNet [61], and VGG16 [62] are all considered the state-of-art.…”
Section: Outlook For the Further Application Of Artificial Intelligence To Mhe Diagnosismentioning
confidence: 99%
“…Moreover, speech and handwriting data can be acquired at low cost and without any distress to the patient. Speech has proven to be a suitable modality for diagnosing Alzheimer's disease [65,66] and Parkinson's disease [67,68]. In the case of AD, the accuracy of the diagnosis depends on the type of speech features used and computational algorithm employed.…”
Section: Outlook For the Further Application Of Artificial Intelligence To Mhe Diagnosismentioning
confidence: 99%
“…Linguistic measures elicited from speech are one type of behavioral indicator that have proved to be useful in predicting cognitive abilities. To this end, studies have considered the use of linguistic measures from transcribed speeches of healthy subjects, or those with different degrees of cognitive impairment in structured clinical assessments [ 18 ]. In fact, it has been shown that language markers predict normal and pathological cognitive functioning [ 19 ].…”
Section: Introductionmentioning
confidence: 99%